Prevalence and interference of neuropathic pain in the quality of life in patients with knee osteoarthritis - Helito, Camilo Partezani; Moreira, Fernando Sant’Anna; Santiago, Matheus Augusto Maciel; Medeiros, Lucas de Faria Barros; Giglio, Pedro Nogueira; Silva , Andre Giardino Moreira da; Gobbi, Riccardo Gomes; Pecora, Jose Ricardo (Clinics, 2023)
Objective: With the aging of the population, more patients have complained of pain due to knee Osteoarthritis (OA), and the number of arthroplasties has also increased. The objective of this study is to evaluate the prevalence of the neuropathic pain component in candidates for Total Knee Replacement and the effects of this component on their quality of life. Methods: In this cross-sectional study, patients with OA candidates for knee arthroplasty in the present institution were evaluated using the pain detection questionnaire and the Visual Analog Pain (VAS) scale to measure the pain index and the presence of associated neuropathic pain. In addition, evaluation of the quality of life and functionality using the EQ5D and SF12 questionnaires and their relationship with cases of neuropathic pain were performed. Results: One hundred twenty-six patients were evaluated, and 71.4 % were female. The age ranged from 46 to 85 years, and about 70 % of the patients had some associated clinical comorbidity. Neuropathic pain was present in 28.6 % of the patients evaluated. Patients with neuropathic pain presented worse results in the VAS evaluation, in the care, pain, and anxiety domains of the EQ5D, and in the physical and mental scores of the SF12. Conclusion: Neuropathic pain was present in 28.6 % of the patients with knee OA who are candidates for arthro-plasty. Patients with associated neuropathic pain present a higher level of pain and worse quality of life scores. Recognizing this type of pathology is extremely important in fully monitoring gonarthrosis.